Bioprocess engineering aspects of biodiesel and bioethanol production from microalgae - Halim, R.; Harun, R.; Webley, P.; Danquah, Michael (2013)
© 2013 Springer Science+Business Media New York. All rights reserved. Rapid increase of atmospheric carbon dioxide together with depleted supplies of fossil fuel has led to an increased commercial interest in renewable fuels. Due to their high biomass productivity, rapid lipid accumulation and high carbohydrate storage capacity, microalgae are viewed as promising feedstocks for carbon-neutral biofuels. This chapter discusses process engineering steps for the production of biodiesel and bioethanol from microalgal biomass (harvesting, dewatering, pre-treatment, lipid extraction, lipid transmethylation, anaerobic fermentation). The suitability of microalgal lipid compositions for biodiesel conversion and the feasibility of using microalgae as raw materials for bioethanol production will also be evaluated. Specific to biodiesel production, the chapter provides an updated discussion on two of the most commonly used technologies for microalgal lipid extraction (organic solvent extraction and supercritical fluid extraction) and evaluates the effects of biomass pre-treatment on lipid extraction kinetics.